Biophysical and farm management drivers of soil fertility under African Leafy Vegetable production small-scale systems in Kenya - Enos Onyuka; Godfrey Nambafu; Darius Andika; Samwel Mwonga; Joseph Gweyi -Onyango; Harun Gitari; Franklin S. Mairura (Farming System, 2025)
While several studies have examined soil fertility management systems under key food and cash crops in the Sub-Saharan Africa (SSA) region, there is a knowledge gap on soil fertility management under African Leafy Vegetables (ALV) small-holder farming practices particularly in Kenya. The objective of this study was to evaluate the influence of agronomic management and socio-economic factors on soil chemical fertility in the major ALV production zones in Kenya. Farm surveys were used to gather socio-economic data, while soil sampling was undertaken in all fields to collect soil chemical data. The findings indicated that Kisii County was characterized by higher proportions of wealthy and more educated farmers, with higher frequencies of input applications relative to Kakamega County. The soil pH was highest in Kenyenya, followed by Gucha, Butere, Mumias, and Khwisero. Gucha and Kenyenya had significantly the highest record of soil carbon concentrations of 3.2 and 3.1 %, respectively compared to other sites, such as Butere (2.0 %) and Khwisero (1.8 %), which had similar soil carbon concentrations, with Khwisero having the least (1.5 %) soil C. The highest mean Zn concentration was recorded in Gucha (6.5 mg kg−1), followed by Kenyenya (6.4), Mumias (4.3), Butere (3.1) and Khwisero (3.0). The study showed that soil fertility under ALV farms in western Kenya was influenced by socio-economic factors and agronomic management factors. In general, the soil fertility status in Kisii County was better, compared to Kakamega County. Soil carbon was significantly influenced by site, soil texture, plot distance, fertilizer sources, and organic and inorganic fertilizer application frequencies. Gucha and Kenyenya Sub-Counties had higher SOC levels, averaging at 1.2 and 1.1 % higher, vis-a-vis Butere Sub-County, while Mumias and Khwisero Sub-Counties had lower average SOC levels in contrast to Butere Sub-County. Site differences can differentiate soil nutrient distribution due to inherent differences in soil characteristics and indirect effects arising from localized soil management practices.